Operation of hydropower plants without storage by optimizing the turbine flow. Variations to the optimization model - Blanco, Juan Manuel (Renewable Energy, Biomass & Sustainability, 2024)
Flowing water power plants take advantage of the flows that circulate through the river in which they are implanted. They do not have in their design storage systems that allow the accumulation of river flows for later use. They only have the infrastructures necessary for the conduction of flows and their use. These types of plants are designed and automated to operate between certain flow limits, working with "constant head", using the available flows at any given time. The operating limits are set by the "equipment flow", for which the plant is designed, and the "technical minimum flow", which corresponds to the minimum flow value with which the plant can work, and which depends on each turbine type. This article is a continuation of the research carried out and part of the results of which have been presented in previous congresses. They established the optimization algorithms to take advantage of times of low flow level (dry season) to use the plant's channels as a storage element for flow rates below the technical minimum and to subject the plant to sequential emptying/filling cycles of the same channels, thus allowing energy recovery, which we will call operation by "optimal flow". This article intends to analyze the response of the proposed optimization model to variations in both the design and operation of the power plants in which its implementation is possible. The response of the plant to variations in the usable volume in the channels, the minimum time established for the operation of the plant, as well as the hydrological characteristics of the year of application is presented.